1994
DOI: 10.1111/j.1600-051x.1994.tb00756.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of porcelain laminate veneers on gingival health and bacterial plaque characteristics

Abstract: The aim of this study was to evaluate the response of microbial plaque and gingival inflammation to the placement of porcelain laminate veneers on anterior teeth. 9 patients, 7 female and 2 male (mean age of 30 years), with a total of 35 veneers were examined. The volume of gingival crevicular fluid (GCF), level of neutral proteolytic enzyme activity, gingival index (GI), plaque index (PlI) and plaque bacteria vitality were measured at baseline and after the placement of veneers. The volume of GCF increased af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
1
8
0
1
Order By: Relevance
“…A total of 71.5% of the restored teeth were free from bacterial plaque, which is very similar to the results found in other studies that show that the teeth restored with these types of restorations have less plaque than other materials 5 years clearly contribute results that are scientifically very useful, although sometimes obsolete as far as the mate used in dental restoration, even including the dental enamel, given that plaque is easily eliminated from these types of surfaces and/or because the life of the bacterial plaque is significantly reduced on the porcelain material itself (17). In 21.7% of the teeth restored with porcelain laminate veneers, bleeding occured on probing.…”
Section: Discussion Of the Resultssupporting
confidence: 79%
“…A total of 71.5% of the restored teeth were free from bacterial plaque, which is very similar to the results found in other studies that show that the teeth restored with these types of restorations have less plaque than other materials 5 years clearly contribute results that are scientifically very useful, although sometimes obsolete as far as the mate used in dental restoration, even including the dental enamel, given that plaque is easily eliminated from these types of surfaces and/or because the life of the bacterial plaque is significantly reduced on the porcelain material itself (17). In 21.7% of the teeth restored with porcelain laminate veneers, bleeding occured on probing.…”
Section: Discussion Of the Resultssupporting
confidence: 79%
“…In a trial of porcelain laminate veneers, Kourkouta et al. (63) found a decrease in the plaque index and bacterial vitality between teeth with and without veneers in the same patients. This finding is consistent with other studies that have shown highly glazed porcelain retains less plaque than enamel (85, 123).…”
Section: Dental Restorationsmentioning
confidence: 99%
“…Örneğin bir araş-tırmada porselen laminate veneer kronların DOS miktarını artırabileceği gösterilmiştir. 103 Soğuk akrilikten hazırlanmış restorasyonlarda da benzer bir etki izlenmiştir. 104 Konservatif dental tedavi işlemlerinin de DOS üzerinde benzer bir etkisi mevcuttur.…”
Section: Dental Tedavilerunclassified